Selection of Six Anterior Teeth for Edentulous Patients - R Masoomi; M Memarian (Tehran University of Medical Sciences, 2005)
Statement of Problem: Choosing an appropriate tooth for edentulous patients is a very important step indentistry.Purpose: This research has been done for determination of proper procedure for tooth selection in edentulous patients.Methods and Materials: In this cross- sectional study 100 student and people who have come to a medicalcenter (range 20-30 years old) were collected randomly and the size of their anterior teeth were determined. A gauge with 0.01 mm accuracy and flexible plastic millimeter was used in order for measurement of anatomic landmark. For achieving the relation between the sizes of teeth statistical analysis was done.Results: 50% of patients were female and the other 50% were male. We found a relationship between mesiodistal width of six maxillary anterior teeth and mesiodistal width of six mandibuMary teeth that can beshown as follow;In men: six mandibular anterior teeth width= 0.S3 * width of six maxillary anterior teeth -2.008 In women: six mandibular anterior teeth width- 0.56 * width of six maxillary anterior teeth + 9.53 Also strong meaningful relationships between width of six anterior maxillary teeth and the width between corners of the lip in curve position have been noticed only in men which can be show' as follow: width of Six mandibular anterior tceth= 39.63 + 0.21+ the width between corners of lip in curve position for men Conclusion: Although there are different ways for prediction of teeth size, it seems these findings can be helpful in determining and prediction of it.